Pemberdayaan, Pelatihan dan Sertifikasi Instruktur Senam Pencegahan Osteoporosis - Widowati, I Gusti Ayu Rai; Manuaba, IA Ratih Wulansari; Sutema, IA Manik Partha; Putra, IGNA Windra Wartana; Suryaningsih, NP Aryati; Dewi, DAP Satrya; Ardinata, I Putu Riska; Maharianingsih, NM (Sekolah Tinggi Ilmu Kesehatan KESDAM IX/Udayana, 2023)
Background: Osteoporosis is a common disease that needs to be treated by a health professional promptly. To address this issue, osteoporosis prevention exercise instructors were trained and certified as part of empowerment initiatives. Purpose: The aims of this program was to create competent, nationally certified instructors. Method: The Indonesian Healthy Bones Community Association (PERWATUSI), a non-profit organization whose objective is to ensure that Indonesians have healthy and strong bones, is responsible for carrying out this empowerment program. The event took place on July 19–20, 2023, in a hall at Bali International University. Results: A total of 59 instructors were selected from various sports communities and trained to provide the public on how to prevent early osteoporosis, conduct suitable exercise program, and emphasize safety training. Before the training started, candidates had to have the necessary educational background, professional qualifications, training in osteoporosis preventive activity, and a commitment to continuing learning. All of participants (100%) met the qualification. Conclusion: These instructors are crucial to the fight against osteoporosis. Those who have earned certification are anticipated to be committed to encouraging healthy lives and lowering the risk of bone fractures.